PERAN PUBLIC RELATIONS DI ERA ARTIFICIAL INTELLIGENCE - Nurislamiah, Mia; Fauzi, Rifqi (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
This research aims to find out how the role of public relations in the era of artificial intelligence. The research method is carried out using a qualitative method that focuses on library research. The data collection technique uses library techniques by collecting library materials related to the object of discussion under study. The results of the literature study show that ways are needed to strengthen data analysis and various skills to remain relevant and effective in the era of artificial intelligence. These include utilising technology and data analysis tools to obtain accurate and clear information, understanding how to process data and create reports that are easy to understand, improving the quality of media relations to remain relevant and effective in the AI era, building good relationships with the media and understanding emerging media trends. Strengthening publication strategies and improving the quality of content presented to the media, responding quickly to communication crises in the era of artificial intelligence, being able to utilise technology and data analysis tools to identify potential crises, and being able to create stand-by statements, draft press releases, and hold press conferences to respond effectively to communication crises.